Bridging Gaps in the Indonesian Emancipated Curriculum Policy: A Systematic Review of Lecturer and Student Challenges - Ro'is, Syamsuddin; Putra, Tomy Kartika; Suprapto (Indonesian Journal of Educational Research and Review, 2024)
The Indonesian government recently introduced the Emancipated Curriculum (EC), also known as Merdeka Belajar-Kampus Merdeka (MBKM), aiming to produce university graduates who are innovative, adaptable, and well-prepared for the demands of the modern workforce. Despite its significant educational reform, limited research has systematically and comprehensively explored the curriculum's complexities. This study adopts a rigorous methodology guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 framework to examine the challenges of EC from the perspectives of lecturers and students. A total of 25 carefully selected scholarly articles were analyzed, revealing key inductive themes. For students, challenges included limited cognitive engagement, difficulties in workplace adaptation, inadequate physical and technological infrastructure, and the complexities of curriculum implementation. For lecturers, issues involved unclear directions regarding EC, challenges in curriculum adjustment, and concerns over the curriculum's overarching paradigm. The findings underscore the urgent need for further developmental interventions to refine the emancipated curriculum and effectively address these challenges. Moreover, the study provides actionable recommendations for future research to enhance the curriculum’s implementation and impact.